Correspondences of Sulayman Basha al-Baruni to Sheikh Ibrahim Abu al-Yaqzan: A descriptive and analytical study - Babaousmail, Zahir (The International tax journal, 2025)
Suleiman Basha al-Barouni -the revolutionary leader and the literary historian- dedicated his life to kindling the spirit of determination for liberation of the Islamic world from the yoke of oppression and restoring its venerable dignity. His relations with the scholars of his era profoundly shaped his character and greatly enriched his knowledge. Among those with whom he closely engaged was his companion at the Qutb institute, Sheikh Abu al-Yaqdhan Ibrahim. Their relationship never ceased despite distance and exile. These correspondences were compiled by Sheihk Abu al-Yaqdhan in his work "The thought of al-Barouni and his eminent status" were later published. The collection offers profound lessons through letters that convey news of his general condition in exile and recall memories and events he exeperienced in M'zab. He also inquired about the scholarly life in M'zab and expressed his views on various academic and jurisprudentical matters. Moreover, it reflects his profound concern for the causes and affairs of the Muslim ummah. Thus, these letters constitute a rich source for elucidating al-Barouni's though and examing his methodology.